Qualifying Teachersâ of English for Specific Purposes to Meet the Global Challenges - Widiatmoko, Paulus; Winardi, Andreas (Ahmad Dahlan Journal of English Studies, 2018)
As institutions of higher education prepare graduates to strive for the more competitive job market, teachers of English for Specific Purposes (ESP) play a pivotal role to nurture and facilitate studentsâ English competence for career advancement. It is commonly hypothesized that ESP teachers require more than that of general English instructors are capable of in language teaching-related pedagogy. However, limited numbers of such studies have been conducted in Indonesia as a potentially developing country in the world. This quantitative study aims to portray ESP teachers perceived qualifications, benefits of the program instruction, and its relevance to meet the challenges of the globalization. Initial findings of this study reveal that almost all of the respondents acknowledged the necessity of ESP teachers to demonstrate capacity in educational principle, language learning theory, Linguistics competence, material and media design, classroom management, intercultural understanding, language assessment, and classroom-based research inquiry. It is perceived that successful ESP teaching is significantly required for graduates to excel the job market, increase professionalism at work, and facilitate the nation competitive edge. Furthermore, ESP programs are considered relevant to meet the present and future challenges of globalization. More elaborative findings will be obtained, specifically addressing difference-variance of perceptions according to respondentsâ education background and teaching experience.